2001
DOI: 10.1016/s0014-5793(01)02639-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of tuf genes: ancient duplication, differential loss and gene conversion

Abstract: The tuf gene of eubacteria, encoding the EF-tu elongation factor, was duplicated early in the evolution of the taxon. Phylogenetic and genomic location analysis of 20 complete eubacterial genomes suggests that this ancient duplication has been differentially lost and maintained in eubacteria. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2004
2004
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 12 publications
0
52
1
Order By: Relevance
“…EF-Tu is among the most slowly evolving proteins known (Lathe and Bork, 2001). The first 300 hits obtained by a BLAST analysis with the N terminus of E. coli EF-Tu in the nonredundant GenBank database covered bacterial EF-Tu sequences from many different species and diverse taxons (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…EF-Tu is among the most slowly evolving proteins known (Lathe and Bork, 2001). The first 300 hits obtained by a BLAST analysis with the N terminus of E. coli EF-Tu in the nonredundant GenBank database covered bacterial EF-Tu sequences from many different species and diverse taxons (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that some orthologs inferred in this study were involved in differential loss after duplication. It has been shown that differential loss and gene conversion might happen after ancient duplication (Lathe and Bork 2001), and gene duplication followed by differential loss can always be invoked as an alternative to lateral gene transfer and vice versa (Gogarten and Townsend 2005). Differential loss will result in a relatively high level of divergence at the sequence level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple independent gene conversion events were detected in outer membrane proteins of H. pylori and C. pneumoniae (Jordan et al, 2001). In another study, gene conversions were also detected by phylogenetic evidence in the tuf genes of different bacteria (Lathe III and Bork, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…Some of them exhibit extraordinary similarity between all its members, which suggests a recent origin after duplication, or a homogenizing mechanism called gene conversion . Gene conversion has been widely documented in diverse multigene families, including the rRNA genes in Escherichia coli (Liao, 2000), tuf in Salmonella typhimurium (Abdulkarim and Hughes, 1996) and Vibrio cholerae (Lathe III and Bork, 2001), pilE in Neisseria gonorrhoeae and N. meningitidis (Haas and Meyer, 1986;Kline et al, 2003), and hop in Chlamydia pneumoniae and Helicobacter pylori (Jordan et al, 2001), among others . Gene conversion also plays essential roles in antigenic variation, an important mechanism in bacterial pathogens to evade the host immune system, as well as other positive and detrimental roles (Deitsch et al, 1997).…”
Section: Introductionmentioning
confidence: 99%